Anchoring Turkey to the EU: Domestic- and Foreign- Policy Challenges - Tocci, Nathalie (Études helléniques / Hellenic Studies, 2004)
Since December 1999, Turkey has formally embarked on an EU accession path. Beyond the rhetoric, however, consensus has not yet been achieved in either Turkey or the European Union on the desirability of a fully European Turkey and on the necessary transformation of the country that this would entail. While Turkey's European orientation is likely to persist, the extent of its depth and the ensuing levels of integration in the EU remain uncertain. Developments in Turkey, Europe and the wider international system will determine the evolution of EU-Turkey relations. In parcicular, the extent and speed of Turkey's reform process and the manner in which Turkey will deal with the foreign policy challenges in its neighborhood will critically affect EU-Turkey relations in the months and years ahead.